Keragaan Pertumbuhan Kalus Sagu Tidak Berduri pada Media MS yang Dimodifikasi - NURHAINI MASHUD (Pusat Penelitian dan Pengembangan Perkebunan, 2009)
Performance of Non-Spiny Sago Callus on Modified MS MediaThe research was conducted in Tissue Culture Laboratory of Indonesian Coconut and Other Palmae Institute, North Sulawesi, in 2008. The aim of the research was to know the growth of callus on modified MS medium. The result indicated that embryogenic callus were formed in 5 to 6 months after subculturing in the media with concentration of 24-D 100 mg/ , where as embryo somatic were formed in 3 to 5 months subculturing in the media with concentration of 2,4-D 50 mg/ . The concentration of 2,4-D is lower for embryo somatic formation than embryogenic callus formation. This result showed that the explant of sago can growth in modificated MS medium.